Climate mobilities: migration, im/mobilities and mobility regimes in a changing climate - Boas, Ingrid; Wiegel, Hanne; Farbotko, Carol; Warner, Jeroen; Sheller, Mimi (Journal of ethnic and migration studies, 2022)
The discussion on the relation between human mobility and climate change has moved beyond linear and exceptional terms. Building on these debates, this article, and the Special Issue on Climate Mobilities: Migration, im/mobilities and mobilities regimes in a changing climate that it introduces, conceptualises this relation in terms of climate mobilities. Through the concept of climate mobilities, we highlight the multiplicity of mobility in the context of a changing climate, including the interrelations between human mobilities and immobilities and their interplay with other mobile flows, such as the mobilities of ideas, information, or climate risk. We furthermore delve into the politics of climate mobilities, defining climate mobility regimes, and implications for mobility justice among those whose mobility is impacted by these regimes. We argue for research to pay more attention to acts of resistance against dominant climate mobility regimes, including voluntary immobilities and re-emplacements that challenge mass migration frames or imposed relocation policies. The articles in this issue empirically examine these dimensions, reflecting on the plurality of climate mobilities and its politics, each analysing how these evolve in a situated cultural or political context.